2011
DOI: 10.2217/rme.10.104
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Bone Marrow Mesenchymal Stromal Cells is Safe for the Lung in a Chronic Myocardial Infarction Model

Abstract: Although the majority of intravenous infused cells were harbored in the lung, they did not cause deterioration of lung function. However, they did not activate the release of inflammatory/anti-inflammatory proteins, or stimulate angiogenesis or myogenesis in the old infarcted myocardium. Thus, intravenous administration of MSCs for chronic MI needs further experimental study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…After intravenous infusion, under normal conditions MSCs are first transiently retained in the lung, before migrating to the liver, spleen and other organs. For individuals with a lung injury, MSCs are retained in the lungs for longer [212][213][214] . In mice with bleomycin-induced lung fibrosis, MSCs have been found to exert a protective effect by ameliorating inflammation and by reducing the degree of injury and fibrosis 210,215 .…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…After intravenous infusion, under normal conditions MSCs are first transiently retained in the lung, before migrating to the liver, spleen and other organs. For individuals with a lung injury, MSCs are retained in the lungs for longer [212][213][214] . In mice with bleomycin-induced lung fibrosis, MSCs have been found to exert a protective effect by ameliorating inflammation and by reducing the degree of injury and fibrosis 210,215 .…”
Section: Stem Cell Therapiesmentioning
confidence: 99%
“…Pulmonary passage is a major obstacle to intravenous stem cell delivery [24]. Although the majority of BMSCs are trapped inside the lungs following intravenous infusion, the 5×10 6 concentration of BMSCs is relatively safe for lungs and does not cause deterioration of lung function in a rat model of chronic MI [25]. Unfortunately, our study indicated that the single intravenous delivery of 5×10 6 BMSCs did not improve the cardiac function in a rat model of DCM.…”
Section: Discussionmentioning
confidence: 92%
“…Promising results derived from preclinical and proofof-concept clinical trials using MSC for cardiac repair have shown their potential to alleviate the deleterious effects of myocardial ischemia [19,20], despite documented poor cell retention after cell injections [21,22]. To achieve widespread clinical application of cell-based therapies for post-ischemic heart failure, the selection of an optimal cell type combined with a therapeutically relevant timing, as well as a well optimized delivery method are crucial.…”
Section: Discussionmentioning
confidence: 99%